Influencer Marketing: Assessing the Effect of Self-Influencer Coungruence, Parasocial Relationships, Credibility and Electronic Word Of Mouth (E-Wom) on Social Media Tiktok - Benedict Peterson; Muh Hilman Hanafi; Jerry S. Justianto (Eduvest - Journal of Universal Studies, 2025)
Purpose – This study aims to explore the impact of social media influencers (SMIs) intimate self-influencer congruence on consumers’ electronic word of mouth (e-WOM), with a focus on the role of parasocial relationships and congruence among the influencer, product and consumer. The study finds its theoretical foundation in parasocial theory and self- congruency theory. Design/methodology/approach – This study employs a quantitative approach, utilizing a sample of 170 collected survey responses. The proposed hypotheses are evaluated using partial least squares structural equation modeling (PLS-SEM). Findings – This study reveals the sequential mediating effect of parasocial relationships and credibility on the link between self-influencer congruence and electronic word of mouth (e-WOM) on TikTok. Credibility plays a significant role in converting parasocial connections into consumer purchase intent. These findings highlight the importance of selecting credible influencers who align with brand values and audience interests to utilize social media marketing. Originality/value – This study brings new perspectives by identifying a limiting factor that shapes the impact of self-influencer congruence on electronic word of mouth (e-WOM) via sequential mediating effect of parasocial relationships and credibility. In doing so, this study provides a novel perspective in understanding the dynamics between SMIs and consumers in the rapidly evolving marketing landscape